How can Christian ideology re-shape jam sessions to enable participants to experience Christian freedom? - Egan, Joseph (2024)
This study was designed to discover how jam sessions can be re-shaped to enable the experience of Christian freedom. It began by suggesting how Christian freedom is relevant to music performance, before outlining five models for jam sessions that align with these principles. These jam session models were tested in workshops and participant feedback was analysed to assess which models best enabled the experience of Christian freedom, of which two types were explored, the first being the traditional Protestant understanding of justification by faith. This is the idea that Christians are made right with God by faith in Christ. This frees them from God’s judgement so that their actions are no longer needed to justify themselves but can be truly of service to their neighbour. The second type is from the new perspective on Paul, which highlights the centrality of forming communities across hierarchical and ethnic boundaries shown in Paul’s epistles. In a musical setting, this means a jam session open to musicians of any background or ability. It found that freely-improvised music games that encouraged participants to focus on each other rather than themselves best enabled both these types of freedom. This study offers a novel way for theology to be applied to music, focusing as it does on ethnographic methods, participant experience and social interaction over aesthetics.